Plans Beyond High School. A Report of a Survey of Statewide Florida High School Seniors, Fall, 1969 - Florida State Board of Regents, Tallahassee; Florida State Board of Regents, Tallahassee ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1970)
This report presents the results of the Fall 1969 statewide survey of the post-high school plans of Florida high school seniors. The students were asked to fill out the instrument: Plans Beyond High School, which requested information of college bound students on the type of institution they planned to attend, whether they planned to go to an in-state or out-of-state institution and their main reason for attending college. Students not planning to attend college were asked their main reason for not doing so, their plans after high school, and whether they planned to attend college later. Those undecided about college were asked their main reason for being undecided. College bound students were also asked to mark the institution they planned to attend. In addition to presenting all the statistical results, this report discusses post-secondary enrollment trends in the state, and analyzes the results in terms of total population, race, sex, 1968 results, intended plans versus actual courses of action, and the non-college bound students and the undecided ones. The final section of the report compares performance on the Florida Twelfth Grade Test of students planning to attend an in-state institution with students planning to attend an out-of-state institution. (AF)
Educational level discussed: Higher Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Academic Aspiration; Academically Gifted; College Choice; Student Motivation; College Attendance; College Bound Students; High School Graduates; Higher Education; Florida